Análise isotópica (Delta15N) e química do capim-marandu adubado com ureia e cama de frango e diferido - Lima, Vania Luzia Fournou de [UNESP] (2014)
Stable isotopes have been used for decades in studies with ruminant animals by reason of isotopic values are based upon not only assimilated food and food eaten. The present study aimed to determine the value of 15N isotopic and chemical composition in natural conditions Marandugrass (Urochloa brizantha. Marandu) under the deferral according to the fertilization used in four cuts after sealing. The work was conducted at the College of Medicine and Veterinary Medicine and Animal Science, UNESP Botucatu. The area, 576m2, used for plots was divided into 3 treatments with 4 replicates each, according to the treatments: T1 - testimony treatment without fertilization; T2 - synthetic organic fertilization with urea and T3 - organic fertilization with poultry litter. After three months, the grass was cut every 15 days, totaling 4 blackout periods. Samples collected in the experiment were analyzed for nitrogen isotopic and chemical composition of crude protein, neutral detergent fiber, acid detergent fiber, cellulose, hemicellulose and lignin. The degradation of poultry litter compost, by the litter bag method was analyzed by regression. Is there a difference for 15N forage compared the treatments, as well as percentage of nitrogen in the forage, percentage of Total Nitrogen in leaf, the leaf 15N, 15N the tiller. To effect the collection was no difference in % Total Nitrogen, % of total N in leaf % N content in stem and % of total N in the tiller. For analysis of crude protein, significant difference between treatments, but when analyzed collections, there were two variables that had differences, crude protein and lignin. The technique of stable isotopes of N was effective in discriminating the inorganic and organic fertilizer on pasture Urochloa brizantha. Marandu deferred and the chemical composition, the source of N did not affect forage quality.